Postinfectious immune-mediated brainstem encephalitis associated with herpes simplex virus infection - Tabarki, Brahim; Kamel, Areej; Anjum, Sher Bahadur; Ezeldin, Kamel; Amin, Adnan (Journal of Pediatric Neurology, 2006)
Postinfectious immune-mediated brainstem encephalitis associated with herpes simplex virus infection is believed to be rare. We report a seven-year-old previously healthy boy who developed brainstem encephalitis with excellent response to acyclovir and methylprednisolone, after herpetic gingivostomatitis. No relapse was noted during a 24-month follow-up period.
Keywords: Herpes simplex virus type 1; brainstem encephalitis; immune-mediated process; steroid therapy